Learning and collaboration technologies : second international conference, LCT 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, proceedings /: second international conference, LCT 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, proceedings. (2015) - Unknown
No abstract available